Physics student worksheet based on science, technology, engineering and mathematics (STEM) to practice creative thinking skill - Khaeruddin Khaeruddin; Jasruddin Jasruddin; Nurhaisa Nurhaisa (Postgraduate, University of Mataram, 2023)
This research is a development research that aims to: describe the feasibility of STEM-based Physics Student worksheets, practitioners' assessment of STEM-based Student Worksheets, the effectiveness of STEM-based Student Worksheets in physics learning, and produce STEM-based Student Worksheets. The subjects of this research trial were 29 students of class XI MIPA at SMAN 15 Luwu. This study uses the ADDIE model development. The instruments used in this study were LKPD validation sheets, practitioner (teacher) response questionnaires, as well as test instruments for understanding creative thinking skills. The eligibility criteria for student worksheets are seen from the aspect of validity. The practicality criteria are seen from the practitioner's assessment of the student worksheets, and the effectiveness criteria are seen from the increase in students' creative thinking skills test results. Based on the results of the analysis, it is concluded that the STEM-based Physics Student Worksheets developed, based on expert assessments, have met valid criteria so that they can be used as learning resources. STEM-based Physics Student Worksheets in terms of the response of physics teacher practitioners are in the very good category and the STEM-based Physics Student Worksheets The work of STEM-based physics students is effectively used to train students' creative thinking skills